Impact of Anti-CD38 Monoclonal Antibody Therapy on CD34+ Hematopoietic Stem Cell Mobilization, Collection, and Engraftment in Multiple Myeloma Patients-A Systematic Review - Flavia Bigi; Enrica Manzato; Simona Barbato; Marco Talarico; Michele Puppi; Simone Masci; Ilaria Sacchetti; Roberta Restuccia; Miriam Iezza; Ilaria Rizzello; Chiara Sartor; Katia Mancuso; et al. (MDPI AG, 2024)
This systematic review examines the available clinical data on CD34+ cell mobilization, collection, and engraftment in multiple myeloma patients treated with the anti-CD38 monoclonal antibodies daratumumab and isatuximab in clinical trials and in real life. Twenty-six clinical reports were published between 2019 and February 2024. Most studies documented lower circulating CD34+ cells after mobilization compared to controls, leading to higher plerixafor requirements. Although collection yields were significantly lower in approximately half of the studies, the collection target was achieved in similar proportions of daratumumab- and isatuximab-treated and nontreated patients, and access to autologous stem cell transplant (ASCT) was comparable. This could be explained by the retained efficacy of plerixafor in anti-CD38 monoclonal antibody-treated patients, while no chemotherapy-based or sparing mobilization protocol proved superior. Half of the studies reported slower hematopoietic reconstitution after ASCT in daratumumab- and isatuximab-treated patients, without an excess of infectious complications. While no direct effect on stem cells was observed in vitro, emerging evidence suggests possible dysregulation of CD34+ cell adhesion after daratumumab treatment. Overall, anti-CD38 monoclonal antibodies appear to interfere with CD34+ cell mobilization, without consistently leading to significant clinical consequences. Further research is needed to elucidate the underlying mechanisms and define optimal mobilization strategies in this patient population.